2013
DOI: 10.1210/jc.2012-2937
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Endogenous Androgens and Abdominal Fat Distribution on the Interrelationship Between Insulin and Non-Insulin-Mediated Glucose Uptake in Females

Abstract: The decreased IMGU in PCOS is not accompanied by a compensatory increase in NIMGU or associated with excessive VAT accumulation. Increased general obesity, SAT, and hyperandrogenism are primary predictors of the deterioration of NIMGU in PCOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 35 publications
3
24
0
1
Order By: Relevance
“…Since the metabolic signatures encompass features related to glucose/insulin metabolism, future studies should investigate closely the relationships between metabolism, visceral adiposity and glucose tolerance classes. Moreover, there is compelling evidence that relationships between abdominal fat distribution and insulin and non-insulin-mediated glucose uptake in females are dependent on endogenous androgens [62], whilst the global adiposity and thickness of intraperitoneal and mesenteric adipose tissue depots have been found increased in women with polycystic ovary syndrome [63]. It will be therefore key in future studies to comprehensively integrate endocrinopathy with metabonomics and other physiological parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Since the metabolic signatures encompass features related to glucose/insulin metabolism, future studies should investigate closely the relationships between metabolism, visceral adiposity and glucose tolerance classes. Moreover, there is compelling evidence that relationships between abdominal fat distribution and insulin and non-insulin-mediated glucose uptake in females are dependent on endogenous androgens [62], whilst the global adiposity and thickness of intraperitoneal and mesenteric adipose tissue depots have been found increased in women with polycystic ovary syndrome [63]. It will be therefore key in future studies to comprehensively integrate endocrinopathy with metabonomics and other physiological parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a chicken-and-egg situation exists between IR and hyperandrogenemia in PCOS, and several in vitro and in vivo studies have demonstrated an improvement in IR through androgen reduction (37,38,39). Additionally, in either pre-or postmenopausal normal women, a direct relationship between androgen levels and IR or DM risk has been determined (40,41). In women with PCOS, but also in controls, androgen levels gradually decrease through time, as has been shown in several studies (42,43,44,45) and confirmed in the present one.…”
Section: Figurementioning
confidence: 99%
“…Primary features of the syndrome include biochemical or clinical hyperandrogenism, ovulatory dysfunction and polycystic ovaries 2 . Other common features include insulin resistance, elevated circulating insulin, and metabolic dysfunction 3 , which may be mechanistically linked to weight gain and obesity in this population 4;5 . In PCOS, elevated insulin may contribute to excess adiposity by limiting fat mobilization and oxidation, thus making weight maintenance and weight loss a significant challenge.…”
Section: Introductionmentioning
confidence: 99%